Peningkatan Aktivitas dan Hasil Belajar Fisika Melalui Model Pembelajaran Student Teams Achievement Divisions (STAD) - Usrotun Marichah (Jurnal Penelitian Pembelajaran Fisika, 2019)
The problem formulation of the research is how the learning process was, how much the students’ physical activity and the result of learning physics through the model's student teams achievement divisions (STAD).  This research was carried out in two cycles and each cycle consisted of three meetings. It was conducted at the class of X MIPA3 SMAN 1 Kedungwuni in the first semester of the school year 2018/2019. There was an increase in the average value of daily tests from 75,17 to 81 and the classical completeness from 66.67% to 91,67%, accompanied by the increase of the student’s activity